(untitled) (Fiep Bulletin - online, 2012)
The birth of the science of human kinetics (CMH), as an epistemological cut, related to the PhysicalEducation, was defended by the author of this study in public PhD exams in 1986. The CMH was then presentedas human being science, focusing on the specialties such as the sport and the motor education (physicaleducation), the ergonomy, the dance, and the psychomotor rehabilitation. The approach used is the one of thecomplexity, where the part is in the whole, and the whole is, at the same time, in the part, which allows the duality inthe center of the unit. And it’s in the scope of a constructivist epistemology, and not in the light of a positivistepistemology, that we will be able to understand the theoretical and practical contributions of the CMH better.There is still one thing to point out: the CMH is born of a epistemological and political view. For Manuel Sergio, theantidualism epistemological is cultural, political, economic and social.